Modegalem matemática do transporte da soja do polo Paragominas-PA: um estudo da viabilidade logística da hidrovia Guamá - Capim - GOMES, Emerson Batista (2023)
This work is located in the field of transport studies and aims to build a mathematical model for transporting soy from the Paragominas Pole-PA to the port complex of Vila do Conde in the municipality of Barcarena-PA, evaluating the feasibility of using the Waterway route Guamá- Capim. To meet this objective, the following were identified and characterized: the producer pole through bibliographical review and data research, the alternative routes that serve the production flow and its port destination and the costs of freight and transshipment of the production. The work is guided by a qualitative approach, configuring a case study supported by multireferentiality given the complexity of the information involved. References such as Cruz (2019) and Fajardo (2001) were used to support the transport dynamics of the soybean theme and Oliveira (2021) and Passos (2008) for the elaboration of the transport model. The proposed model meets the criteria of Linear Programming considering the distances and transport costs comparing the road modal to the waterway-road intermodal. The results show that private and state investments, with the aim of improving the waterway infrastructure of the Paragominas Pole logistics corridor, inland river transport through the Guamá-Capim Waterway can be considered a viable alternative for the transportation of soy production in the region.